Knowledge and practice in preventing fall among obstetrics patients in state hospital in Terengganu - Siti Hajar Muda,; Wan Nur Hafsah Wan Lokman, (Universiti Kebangsaan Malaysia, 2025)
Falls during pregnancy are a typical reason for minor injuries, and they can occasionally be dangerous for both the mother and the unborn child. This study is designed to identify the knowledge and practice in preventing falls among obstetrics patients in Hospital Sultanah Nur Zahirah. This cross-sectional study used a self-reported questionnaire involving women admitted and delivered at a state hospital between October to December 2022. The Pearson Chi-Square test in SPSS software was used to examine associations between sociodemographic characteristics and variables of interest. Overall, 350 postnatal women were selected as the subjects. The mean age of the women was 30.41 ± 5.4 (range: 19-44) years old. Most of the respondents were in parity 2 to 4 (56.3%). Fifty-seven women (16.3%) reported falling at least once during the index pregnancy. The mean score for knowledge was 12.30 ± 3.72, with 16.6% having good knowledge and the mean score for practice was 7.24 ± 4.23, 25.4% of them were having good practice. The women’s knowledge of preventing falls during pregnancy was predicted by their age (χ2 = 19.73, p = <0.05), education (χ2 = 21.582, p = <0.05) and parity (χ2 = 15.208, p = <0.05). The practice of the women about preventing falls was significantly poorer amongst the women who were younger (χ2 = 23.434, p = <0.05), less family income (χ2 = 17.95, p = <0.05), and had no more than a secondary education (χ2 = 14.88, p = <0.05). The findings of the study revealed that age, level of education and parity is associated with knowledge of women in preventing falls. While age, level of education and family income are associated with practice in preventing falls. Hence, awareness campaigns using effective risk communication models are advised to increase knowledge and good practice among pregnant women.